Called Out of Darkness: Presenting Christian Hope to People with Depression - Kleist, Deirdre (Lumen et Vita, 2015)
The world today is in desperate need of hope. In particular, with depression and other mental illnesses coming increasingly to the forefront of society’s consciousness, now is the time for the Church to speak out about true Christian hope. The issue is not that the Church has failed to articulate what makes Christian hope distinct from the more secular understanding of hope. Indeed, in Spe Salvi Pope Benedict XVI offered a thorough examination of hope, its communal nature, and its saving power. He also wrote about the need to care for one another, and to be bearers of the great hope in Christ to all. This message, though, has not clearly or frequently enough been applied to those who struggle with mental illness. Many depressed believers are in fact made to suppress their inner trials so they will not seem to be unfaithful Christians. Those who suffer, whether within or outside of the Church, need to hear about both the great hope that lies beyond this world and the incarnate hope that has come among us. The paper I am proposing would examine the practical pastoral implications of preaching Christian hope to those living in darkness, and of exhorting all Christians to bear suffering together so as to bring communal hope of salvation. Spe Salvi and Scripture would constitute my primary foundation for understanding Christian hope. Looking at the reality of a depressed mindset and the lifelong challenges of those who suffer chronic depression, I intend to craft a refined definition of Christian hope that speaks in a particular way to this population. I would also present strategies for ministers for conveying Christian hope and for practicing both compassion and consolation. This could better equip ministers to serve a population that increasingly finds itself marginalized within the Church.